Education in times of pandemic, teaching and learning at home, new school model. - López Vargas, Sandra Johana (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The present work is elaborated in order to mention the experiences that were registered while the investigative pedagogical practice is developed, this being an atypical experience; In view of the health situation that the country is going through and forcing the population to confine themselves to their homes, a situation that has forced a change in teaching methodologies in the education sector, when carrying out the practice, great shortcomings are evident both in the methodology that is implemented for the development of the themes, such as the socioeconomic cracks in the sector, which reflects the inequality that some families go through, which cannot access the current educational model in the same way. They also want to publicize the advantages and disadvantages that this situation that students go through brings with it, and how the execution of the classroom project is carried out, in this way to be able to provide a reflective look at the process. I consider important the support and commitment of parents for the development of all implemented acade- mic activities.